Intensitas Kegiatan Keagamaan dan Pengaruhnya Terhadap Perilaku Sosial Islami Siswa MTs Nurul Iman Modong Pali - Rozikin; Sialam (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2021)
This research was motivated by the existence of religious activities at MTs Nurul Iman. Whether with religious activities at school, students are accustomed to carrying it out in everyday life. As for religious activities that exist in the community, namely congregational prayer, general recitation, yasinan, zakat, commemoration of Islamic holidays and so on. Religious activities and religious practices organized by an institution and followed on a regular basis can create habituation to proper Islamic behavior according to Islamic teachings. This research method is quantitative with 32 students as respondents. The sample was taken using proportionate stratified random sampling technique. Independent variable: intensity of participating in religious activities, dependent variable: Islamic behavior of students. Sources of data from respondents and documents. Data collection techniques using questionnaires and documentation. The data analysis technique used the validity test, the Pearson correlation coefficient. The results showed that (1) There was a positive and significant influence between the intensity of participating in religious activities on Islamic behavior of students, the results of the analysis of the calculated analysis. Based on the research, it was found that the correlation index number was 0.870. Then this figure is interpreted using the rtabel value table, it turns out that rxy is greater than rtable, both at the 5% significance level and at the 1% significance level. (2) The supporting factors for Islamic religious teachers in implementing the formation of student behavior at MTs Nurul Iman Modong are located In a good environment, there are strict rules and sanctions, the existence of Citizenship Education subjects, and there is support from Islamic Education teachers who insert values ??????of behavior at every opportunity. While the inhibiting factors are the lack of attention from parents of students and the lack of intensity in participating in religious activities, the attention and discipline of teachers in schools, thus hampered in the formation of student behavior.